GAMBARAN LENGKUNG SENYUM PASIEN DENGAN USIA MINIMUM 15 TAHUN SEBELUM DAN SESUDAH PERAWATAN ORTODONTI CEKAT - Sarinah Rambe (Journal of Syiah Kuala Dentistry Society, 2016)
AbstractGenerally, the aim of orthodontic treatment is to improve the occlusion, masticatory function, the oralhealth as well as to obtain optimal facial aesthetics. Adolescence are more interested in socializingphysical attractiveness. Arch smile can affect facial aesthetics. This study aimed to compare the smilearch in patients coming to the clinic specialist orthodontic FKG USU before and after fixed orthodontictreatment in 2004-2011. The study was conducted on 23 people based inclusion and exclusion criteria.The results were obtained p = 0.453 and = 0.05 (p ), it can be concluded that there was nosignificant difference between the arch smile before and after fixed orthodontic treatment. Theconclusion there is correcting the patient's smile became more attractive after fixed orthodontictreatment.Keywords: Smile, Smiles Aesthetic, Smile Arch, Fixed Orthodontic